Telaah Kebijakan Undang-Undang Pesantren Melalui Pendekatan Multidisipliner - Safaruddin Yahya (Journal on Education, 2023)
This paper aims to explain the policy of the Islamic Boarding School Law as an affirmation of the importance of Islamic boarding schools as moderate educational institutions. Islamic boarding schools, in addition to Da'wah and Education Institutions, are a forum for community empowerment, through teaching various skills and empowering the people's economy, and many other aspects that are often worked on by Islamic boarding schools. This article explores the process of formulating the Islamic Boarding School Law, what are the basic things that emerge as policies from the Islamic Boarding School Law and how it impacts the sustainability of Islamic boarding schools.